Status Hukum Anak Angkat Tanpa Penetapan Pengadilan Agama dalam Hukum Positif di Indonesia: Studi Kasus di Kelurahan Cengkeh Turi Binjai Utara - Dwi Andreyan Syaputra; Fauziah Lubis (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
This study aims to analyze the legal status of adopted children without a court in positive law in Indonesia, focusing on a case study in Cengkeh Turi Binjai Utara Village. A major problem related to the legal status of adopted children arises because of the adoption of children without a court determination. A child who is adopted without court approval does not have a clear legal status, which can affect his rights in several ways, such as inheritance rights, civil rights, and legal protection from exploitation or abuse. This study uses an empirical juridical approach, with a data collection method through interviews and observations of the local community and related parties. The results of the study show that the practice of child adoption in these areas is often carried out based on informal agreements between families, which ignores the legal procedures regulated in Law Number 35 of 2014 concerning Child Protection and Government Regulation Number 54 of 2007. This results in adopted children not getting adequate legal protection, and is at risk of exploitation and loss of their basic rights. Meanwhile, in mawaris fiqh, the adoption of children without a court decision has various consequences. Islamic law allows the adoption of children only to nurture, care for, and educate them as long as their blood relationship with their biological parents is not severed.